Iceland’s External Affairs from the Napoleonic Era to the Occupation of Denmark: Danish and British Shelter - Baldur Þórhallsson 1968-; Tómas Joensen 1981- (2015)
Fræðigreinar This paper argues that Iceland enjoyed essential shelter, for its development and prosperity, provided by Denmark and Britain. Societal relations with Copenhagen were of fundamental importance in the preservation and evolution of Icelandic identity and culture, providing the foundation of the modern society and leading to the establishment of the Icelandic state. Danish financial backups created the basis for the island’s economic prosperity in the 20th century. Moreover, Denmark provided partial political shelter in terms of significant diplomatic support in guaranteeing trade agreements with other states. Also, Denmark led by example and Iceland followed its foreign policy. On the other hand, Denmark failed to provide Iceland with protection of its land and waters and economic cover when it was in most need. Moreover, the economic cover it did provide was, at times, highly costly. Denmark had been downgraded to a small European power in the post-Napoleonic period. In practice, Britain was in control over the North Atlantic. It guaranteed Iceland’s neutrality and connection to the outside world and markets when the Danish authorities failed in these areas, as long as British interests were also served. Nor did British protection come without cost. Accordingly, this paper confirms the common claim of small-state studies that small states are at the mercy of their larger neighbours. Moreover, our findings indicate that Iceland’s growing autonomy did not affect its need for political, economic and societal cover.